1990
DOI: 10.1111/j.1651-2227.1990.tb11416.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of β‐Endorphin and Substance P in the First Year of Life in Full‐Term and Preterm Infants

Abstract: 2 7 . 2 2 6.2 pg/ml, r,=0.402, p<0.05). SPLI 38.327.7, r,=0.229) this correlation could not be found (Fig. 3).Thus prematurity must be considered as a decisive factor for the altered plasma levels of P-EDLI and SPLI also if the age is corrected for a gestational age of 40 weeks. This may indicate the immature state of development of preterms in comparison with full-terms of the same age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Eleven per cent of the plasma SP results from the current study yielded a value of 0.0 pmol/L, but these were probably genuinely undetectable concentrations as NKA remained detectable in all the same samples, with concentrations ranging from 2.6 to 45.0 pmol/L (median 6.6 pmol/L). Moreover, other investigators have also reported undetectable concentrations of plasma SP not only in infants, 9 but also in adults. 1012 In addition, we now know that unextracted plasma gives higher concentration measurements than extracted samples, and hence the accuracy of other published reports on high plasma SP concentrations (300–500 pmol/L) where sample extraction had not been performed 1315 may be open to question.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Eleven per cent of the plasma SP results from the current study yielded a value of 0.0 pmol/L, but these were probably genuinely undetectable concentrations as NKA remained detectable in all the same samples, with concentrations ranging from 2.6 to 45.0 pmol/L (median 6.6 pmol/L). Moreover, other investigators have also reported undetectable concentrations of plasma SP not only in infants, 9 but also in adults. 1012 In addition, we now know that unextracted plasma gives higher concentration measurements than extracted samples, and hence the accuracy of other published reports on high plasma SP concentrations (300–500 pmol/L) where sample extraction had not been performed 1315 may be open to question.…”
Section: Discussionmentioning
confidence: 93%
“…Scholle et al 9 reported mean (standard error) plasma SP concentrations of 20.2 (4.6) pmol/L in 32 preterm infants, and 28.4 (5.7) pmol/ L in 19 term infants. 9 However, the results in Scholle's study were from unextracted plasma samples, which can yield higher concentrations of SP due to antibody cross-reactivity. There was also no description of sample handling and preservation procedures, which has been shown to be of importance (CMW, data published in PhD thesis).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations